1999
DOI: 10.1165/ajrcmb.20.1.3321
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Perlecan and Tropoelastin Gene Expression and Cell Replication in the Developing Rat Pulmonary Vasculature

Abstract: Smooth-muscle-cell (SMC) replication and extracellular matrix protein expression are two vital and interrelated processes necessary for normal development of the vasculature. To understand better the nature of this relationship in the developing rat lung, we investigated the relationship between SMC proliferation and the expression of perlecan, a basement membrane (BM) heparan sulfate proteoglycan implicated in the control of SMC growth and differentiation, and tropoelastin (TE), a structural matrix protein no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Previous data from our laboratory demonstrated that pulmonary artery and airway SMC and airway epithelial cell replication rates during development parallel those observed for aortic SMCs, 18 suggesting that an intrinsic, developmentally timed mechanism controls the replication of a variety of cell types. We examined the expression of emb8:EGAP mRNA in the developing rat lung, a tissue known to undergo extensive remodeling throughout intrauterine and early postnatal life.…”
Section: Resultsmentioning
confidence: 58%
“…Previous data from our laboratory demonstrated that pulmonary artery and airway SMC and airway epithelial cell replication rates during development parallel those observed for aortic SMCs, 18 suggesting that an intrinsic, developmentally timed mechanism controls the replication of a variety of cell types. We examined the expression of emb8:EGAP mRNA in the developing rat lung, a tissue known to undergo extensive remodeling throughout intrauterine and early postnatal life.…”
Section: Resultsmentioning
confidence: 58%
“…However, these studies were conducted in adult models and cells and may have limited relevance to the fetal pulmonary vasculature. In the developing rat lung, maximal SMC proliferation occurred during the embryonic period, followed by a decline in the fetal period and a steady decrease after birth (5). Furthermore, the decrease in proliferation was associated with an increase in the expression of perlecan, which was predominant in nonreplicating cells.…”
Section: Discussionmentioning
confidence: 96%
“…Perlecan was shown to negatively correlate with SMC proliferation (30), and it was shown to inhibit Oct-1, a growthrelated transcription factor (31). In certain cell types, however, blocking perlecan production via antisense DNA inhibited cell growth (32)(33)(34).…”
Section: Figmentioning
confidence: 99%